Resiliensi pelajar komunitas Kawruh Jiwa dalam menghadapi pandemi COVID-19 - Rahmadi, Sidiq; Aji, Danag Bimo; Lestari, Sri (Universitas Brawijaya, 2023)
Excessive information about COVID-19 comes and goes, causing panic and psychological pressure. It takes awareness of reality and resilience in dealing with uncertain conditions. This study aimed to determine the resilience of the Kawruh Jiwa community students in facing a pandemic. The Phenomenology descriptive qualitative research method with data collection techniques using semi-structured interviews and literature review. The informants of this study were two people aged 51 and 45 years who were determined using a probability sampling technique. The data were analyzed thematically by understanding, analyzing and determining the aposterior coding theme. The results of this study reveal that the teachings of Kawruh Jiwa have a role of self-control when facing reality that is faced with mikir leres (think right), ngudari raribet (unravel commotion), mengenal rasa (recognize feelings), tatag (be steadfast) dan mawas diri (be vigilantly applied) by Kawruh Jiwa students can develop resilience when facing the COVID-19 pandemic.